Service Quality as a Strategic Driver of Competitive Advantage: A SERVQUAL-Based Empirical Study in the Steel Industry - Sabrina Ghusyi Nova; Sukaris (LP2M IAIN Palopo, 2026)
This study aims to evaluate differences in digital-based service quality that can be used as a competitive advantage in the B2B steelmaking industry, focusing on a case study of PT Ravana Jaya. This study examines the dimensions of responsiveness, reliability, and assurance within the SERVQUAL framework and their influence on repeat orders from customers. The method applied is a descriptive qualitative approach through in-depth interviews with five key informants, operational observations, and analysis of internal company documents during the period from August to September 2025, using the data analysis model from Miles and Huberman. The research findings indicate that there are significant differences in the responsiveness dimension due to limited digital readiness of services, as seen from the reliance on manual communication without a CRM system or customer portal. This study emphasizes that digital service responsiveness plays a role as an important indicator of customer loyalty and competitive advantage in the medium-sized steel fabrication sector. From a practical perspective, these results emphasize the importance of integrating CRM and real-time digital services as a strategy to increase competitiveness sustainably.